Wacana Penolakan terhadap Pengungsi Rohingnya di Indonesia - Sari, Diajeng Nilam (Research Community for Critical Society and Environment, 2024)
Mass media is a tool for disseminating information and ideas widely. Through discourse analysis, an ideology can be found in the news from the media. Discourse analysis aims to reveal a meaning or message contained in a text both textually and contextually. The purpose of this study is to analyze the discourse on the rejection of ethnic Muslim rohingya refugees in Indonesia in the December 11, 2023 edition of voaindonesia.com media. This study uses critical discourse analysis according to Norman Fairclough, namely the microstructural, mesostructural, and macrostructural dimensions. The results of this study show that voaindonesia.com media shows alignment towards the people of Aceh based on the analysis of three dimensions of microstructural, mesostructural, and macrostructural which are all interconnected and complement each other.